Algorithm PSO for maximum coverage of users using drones to find optimal points for deployment - Fariborz Rasouli (Computational Algorithms and Numerical Dimensions)
Today, drones have effective and significant functions in various fields, including assistance, rescue, discovery, surveillance, etc. One of the uses of these air vehicles is to use them as Air Base Stations (ABS). It is obvious that ground base stations do not have the ability to cover users everywhere and all the time. For this reason, using the Particle Swarm Optimization (PSO) algorithm, we try to introduce drones as ABS to find the maximum coverage of users in the shortest possible time. Compared to ground stations, drones have limited power and energy. In this regard, placing drones as ABS should be done with less energy consumption. From this point of view, finding optimal points in order to cover users and provide Quality of Service (QoS) and stable and reliable data rate in ABS is more sensitive and requires optimality. In this article, it has been tried to analyze the optimal points for the deployment of drones in the shortest possible time by analyzing the PSO algorithm in order to provide services to different users, simulated and examined from different aspects. So that users can always and everywhere has acceptable and affordable communications in the shortest possible time.